The Influence of NU’s Bahtsul Masail Fatwas on the Development of National Law - Muzawwir Muzawwir (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
Islamic law is an integral part of national law, the results of the NU LBM Fatwa are part of Islamic Law which is fatwaed to answer religious, economic, social, legal, political and other aspects, of course the results of the fatwa are very influential on the development of national law, because First, the results of the NU LBM fatwa are very dynamic in accordance with the conditions and the surrounding environment which are part of the dynamics of national and state life that cannot be separated from the basic foundations of the Quran and Hadith. Second, because of the capacity and quality of knowledge of the Ulama and NU intellectuals who took part in the implementation of Istinbath Hukum by LBM NU. Abstrak: Hukum Islam merupakan bagian integral dari hukum nasional, hasil Fatwa LBM NU merupakan bagian dari Hukum Islam yang difatwakan untuk menjawab permasalahan-permasalahan keagamaan, sosial budaya, ekonomi, politik dan aspek lainnya, tentunya hasil fatwa tersebut sangat berpengaruh terhadap pembangunan hukum nasional, karena, Pertama, hasil dari fatwa LBM NU sangat dinamis sesuai dengan kondisi dan linkungan sekitar yang menjadi salah satu dari sendi-sendi kehidupan berbangsa dan bernegara yang tidak terlepas pada landasar dasar Al-Quran dan Hadist. Kedua, karena kapasitas dan kwalitas ilmu para Ulama serta para intelektual NU yang sangat berperan dalam pelaksanaan Istinbath Hukum oleh LBM NU.